1989
DOI: 10.1002/abio.370090306
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a promoter‐probe vector for the methanol‐utilizing bacterium acetobacter methanolicus MB 58

Abstract: We report here the construction of a promoter-probe vector, pRS2, which can be utilized in either Acetobacter methanolicvs MB 58 or Escherichiu .wli due to the presence of broad-host-range replicon RSF 1010. The vector provides several unique restriction sites for promoter cloning as well as resistance markers for the selection of transformanta. The promoter-probe vector was constructed by inserting a n EceoRI-13alI-polylinker fragment-of pUC 19 into EeoRI/SalI digested pMK 16. The resulting plasmid, pRS1, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As described before, the AAB genus Acidomonas was established since several characteristics of the former species Acetobacter methanolicus could be distinguished from other type and representative AAB including Acetobacter strains, resulting in the renaming of A. methanolicus to Acidomonas methanolica (Urakami et al 1989 ). For Acidomonas expression vectors including a basic promoter probe vector have been created based on the popular broad-host-range multi-copy plasmid RSF1010 (Schröder et al 1989 ; Schröder et al 1991 ). In A. methanolica , a RSF1010-based derivative was used to express the core antigen gene of hepatitis B virus subtype ayw under control of the E. coli P lac promoter alone and under tandem control of the strong promoter P acm from the Acetobacter phage Acm l and from P lac .…”
Section: Target Gene Expression In Acidomonasmentioning
confidence: 99%
“…As described before, the AAB genus Acidomonas was established since several characteristics of the former species Acetobacter methanolicus could be distinguished from other type and representative AAB including Acetobacter strains, resulting in the renaming of A. methanolicus to Acidomonas methanolica (Urakami et al 1989 ). For Acidomonas expression vectors including a basic promoter probe vector have been created based on the popular broad-host-range multi-copy plasmid RSF1010 (Schröder et al 1989 ; Schröder et al 1991 ). In A. methanolica , a RSF1010-based derivative was used to express the core antigen gene of hepatitis B virus subtype ayw under control of the E. coli P lac promoter alone and under tandem control of the strong promoter P acm from the Acetobacter phage Acm l and from P lac .…”
Section: Target Gene Expression In Acidomonasmentioning
confidence: 99%
“…3. In comparison with the plasmid pRCF1, which contains only the promoter of the cloned DNA fragment, the specific homoserine dehydrogenase activity increased by 2 to 3 fold in the plasmid pRCFtac containing the tac promoter in the tandem position and by 5 fold in the plasmid pRCF119 containing the acml phage promoter.…”
Section: Transfer and Expression Of The Ptlb Gene In E Coli And A mentioning
confidence: 99%
“…These plasmids can be transferred to and be stably maintained in many gram-negative bacteria, including the acidophilic methanol-assimilating bacterium A. methanolicus. One of the most popular plasmids used for this purpose is the multicopy number plasmid RSFlOlO [2], which can be mobilized into A. methanolicus by a triparental mating technique using pRK2013 as a helper plasmid [3]. An optimal expression of a foreign gene in a given host requires an optimal initiation of transcription and translation.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work it was shown that the broad-host-range plasmid RSF1010 and its derivatives can be mobilized and stably maintained in this methylotrophic bacterium (SchrSder et al 1989). Therefore, constructed plasmids derived from RSF1010 were transferred via mobilization into the new host using pRK2013 as helper plasmid.…”
Section: Expression O F the Core Antigen Gene O F H B V In E Coli Anmentioning
confidence: 99%